Re-interpretation of Geophysical Data for the Archaeological Hill “Malta” at Duhok City – Iraqi Kurdistan Region - Ghaib, Fadhil A.; Gardi, Sirwa Q. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Two geophysical methods (gravity and resistivity) are used to investigate the Malta archaeological hill in Duhok City-Iraqi Kurdistan Region. 200 gravity observation points were occupied covering the southern half of the flat-top of the hill. Precise Bouguer anomaly map and its regional, residual and Second Vertical Derivative anomalies are constructed to show the anomalous remains. High precision altitudes and accurate positioning of the stations guaranteed reasonable reductions. Beside gravity, six resistivity traverses are executed along selected directions. A total of 84 Vertical Electrical Sounding resistivity measurements along traverses were taken to show variations with depth. A final model of the subsurface was derived by the integration of both geophysical approaches. The two geophysical methods revealed the presence of wall remains distributed in a systematic manner under the surface. Their depth ranges from 0.5m to 1.5m. They are mostly built of limestone rocks of high resistivity and positive gravity anomalies.
Keywords: Archeogeophysics Malta Hill Duhok City Iraqi Kurdistan